Semiotic analysis of a media text the Lord of the Rings : The Fellowship of the Ring. - Setia, Roszainora; Osman, Maziana; Abdullah, Shazila; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
The Lord of the Rings movie by Peter Jackson was an interesting genre for semiotic analysis. This brief analysis w as looking at the manner of intertextuality, style and form, as well as a syntagmatic analysis. It also discussed the aspect of signs and the signified. The signs employed by filmmaker Peter Jackson in constructing this media text can be categorized in to social codes, technical codes and representational codes.